Enhanced efficiency phosphorous fertilizers on the coffee crop in sandy soil - R. Guelfi, Douglas; A. Reis Jr, Roberto dos; F. T. Chagas, Wantuir (International journal of Horticulture, Agriculture and Food science, 2021)
Crops are generally cultivated in deficient phosphorus soils in the tropics. Phosphorus (P) is essential to crop development and has a low efficient use in fertilizer management. The need to increase P fertilization efficiency justify studies evaluating the performance of enhanced efficiency P fertilizers. A greenhouse experiment was carried out to evaluate coffee growth, plant P contents, and agronomic P fertilization efficiency. The treatments, randomly designed with three replicates, were arranged in a 2x5 factorial scheme: two P sources (Triple Superphosphate – TSP and Policote coated TSP – TSP+Policote) and five P rates (0; 5; 10; 15 and 20 g P2O5.plot-1). The experimental plot was formed by a pot with 14 kg of sandy soil. All treatments were homogenized with the plot's soil. Then, coffee seedlings were transplanted. Coffee growth, plant P content and accumulation, and agronomic P fertilization efficiency were affected by phosphorus fertilization. TSP+Policote promoted higher leaf and plant dry matter yield and P accumulation in coffee than conventional P fertilizer. The higher agronomic efficiency and apparent P recovery efficiency index, observed with TSP+Policote, explain the higher coffee plant growth observed with Policote coated P fertilizer. The obtained results demonstrated that Policote coated P fertilizer can be used as an enhanced efficiency fertilizer. Results show that Policote coated P fertilizer is a more efficient way to deliver the required P to plants.